MEDIA FRAMING AND THE RISING NATURE OF SUPPORT FOR RIGHT-WING POPULISM: THE CASE OF THE CZECH REPUBLIC - Makhtayeva, Aisulu (Nazarbayev University School of Sciences and Humanities, 2023)
The academic literature does not provide a convincing and comprehensive explanation for the impact that media framing has had on the growing support for right-wing populism in the Czech Republic. To fill the gap in the literature, this thesis empirically explores the issues that are framed in the media, which results in the increasing support for right-wing populism, the proxy for which is the votes given to populist parties in the Czech parliamentary elections over the course of the past years. After it was determined that factors such as immigration, crime rates, and unemployment rates are highly associated with the popularity of right-wing populism, content analysis and personal interviews were conducted to understand whether or not the media framing plays a role in the rising support for right-wing populists. In spite of the fact that the rate of immigration in the Czech Republic is significantly lower than in the other countries of the European Union, the findings suggest that media framing has an indicative influence on the outcome of electorate results due to the large pool of newspaper consumers in the Czech Republic.
Keywords: Type of access: Restricted; right-wing populism; Czech republic; Media